2019
DOI: 10.1002/ange.201912994
|View full text |Cite
|
Sign up to set email alerts
|

To Sandwich Technetium: Highly Functionalized Bis‐Arene Complexes [99mTc(η6‐arene)2]+ Directly from Water and [99mTcO4]

Abstract: The labeling of (bio)molecules with metallic radionuclides such as 99mTc demands conjugated, multidentate chelators. However, this is not always necessary since phenyl rings can directly serve as integrated, organometallic ligands. Bis‐arene sandwich complexes are generally prepared by the Fischer–Hafner reaction. In extension of this, we show that [99mTc(η6‐C6R6)2]+‐type complexes are directly accessible from water and [99mTcO4]−, even using arenes incompatible with Fischer–Hafner conditions. To unambiguously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 37 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…Experimental methods, synthetic procedures, analytical data and NMR assignments are described in the Supporting Information for all compounds. In this section only the procedures of the key compounds [4](TFA), [5](TFA), [8](TFA), [10](OTf) and [12](TFA) are given. Complexes [1](OTF), [2](TFA) and [3](TFA) were synthesized according to literature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental methods, synthetic procedures, analytical data and NMR assignments are described in the Supporting Information for all compounds. In this section only the procedures of the key compounds [4](TFA), [5](TFA), [8](TFA), [10](OTf) and [12](TFA) are given. Complexes [1](OTF), [2](TFA) and [3](TFA) were synthesized according to literature.…”
Section: Methodsmentioning
confidence: 99%
“…HPLC 2). The product containing fractions were combined and the solvent was evaporated to yield [8](TFA) as an orange solid. Yield: 40.8 mg (0.064 mmol, 49 %).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the configuration of the incoming arenes, some interesting stereochemical features become evident. Multisubstituted arenes such as 2,4-dimethylaniline (4), carbazole (10) or melatonin (12) can coordinate from both sides, from Up Figure 1. Ellipsoid displacement plots of complexes [Re(η 6 -4) 2 ] + (5 + , 2,4-dimethylaniline, one isomer), [Re(η 6 -6) 2 ] + (7 + , mequinol), [Re(η 6 -8) 2 ] + (9 + , lidocaine) and [Re(η 6 -6)(η 6 -napht)] + (14 + ).…”
Section: Stereochemical Featuresmentioning
confidence: 99%
“…In a follow up study, we showed that complexes [ 99m Tc(η 6 -arene) 2 ] + with arene being functionalized phenyls, are accessible in water in one step and directly from [ 99m TcO 4 ] À . [10] This approach offers a general approach to directly labelled pharmaceuticals according to structure D in Scheme 1. It is thus not necessary to introduce additional chelators.…”
Section: Introductionmentioning
confidence: 99%